When ESG Meets Politics: The Role of Political Connections in Enhancing Firm Value in Indonesia - Al Putri Oktavia; Armadani Armadani; Liza Ulfiana; Arif Mahasin Sondani (Owner : Riset dan Jurnal Akuntansi, 2026)
The purpose of this study is to examine the effect of ESG performance on firm value. Furthermore, this study also empirically analyzes the moderating role of political connections on the relationship between ESG performance and firm value. This study analyzes non-financial companies listed on the Indonesia Stock Exchange from 2016 to 2023, totaling 1,644. The hypotheses are tested using panel data regression. We also conduct several other tests, such as robustness tests and additional analyses, to deepen the study. This study reveals that ESG performance increases firm value. Furthermore, political connections strengthen the positive effect of ESG performance on firm value. Additional tests align with the main findings. Interestingly, when separating large and small firms, only large firms significantly influence both the direct influence of ESG on firm value and the role of political connections in strengthening this relationship. This study fills an important gap by providing large-sample evidence from an emerging market and demonstrating that political connections are not merely direct value drivers, but institutional mechanisms that amplify the market relevance of ESG practices.